2022
DOI: 10.1155/2022/9334079
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fe Doping on Photocatalytic Dye-Degradation and Antibacterial Activity of SnO2 Nanoparticles

Abstract: A simple hydrothermal method is utilized to synthesize iron-doped tin oxide nanoparticles (Fe-SnO2 NPs) at various doping concentrations. The structural characterization using XRD, Raman, and FTIR measurements confirmed the incorporation of Fe ions into the SnO2 lattice without any deviation in the tetragonal crystal system of SnO2 nanoparticles. SEM and HRTEM images show the spherical-shaped nanoparticles with agglomeration. The values of interplanar spacing ( d … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The following are the charge transfer and creation mechanisms of the active degrading species or the redox reaction during the photocatalytic processes: (11)(12)(13)(14)(15)(16) shows that during the photocatalytic reaction, the oxygen molecules received from the air or water combine with the freely mobile photogenerated electrons in Cu-SnO 2 to form peroxide radicals O 2 *− while the photogenerated holes in the valance band of ZnO react with water to produce H + and OH * . The hydroxyl radicals are a stronger degrading species having a high redox potential nearly equals to valance band edge potential (2.89 eV).…”
Section: Ementioning
confidence: 99%
See 1 more Smart Citation
“…The following are the charge transfer and creation mechanisms of the active degrading species or the redox reaction during the photocatalytic processes: (11)(12)(13)(14)(15)(16) shows that during the photocatalytic reaction, the oxygen molecules received from the air or water combine with the freely mobile photogenerated electrons in Cu-SnO 2 to form peroxide radicals O 2 *− while the photogenerated holes in the valance band of ZnO react with water to produce H + and OH * . The hydroxyl radicals are a stronger degrading species having a high redox potential nearly equals to valance band edge potential (2.89 eV).…”
Section: Ementioning
confidence: 99%
“…However, merely transition metals doping did not enhance the photocatalytic efficiency of SnO 2 nanoparticles. For instance, Preethi et al (2022) reported that the photocatalytic efficiency of visible light-assisted Fe-SnO 2 nanoparticles catalyst was 43% for the degradation of Methylene blue dye [16]. Besides, the construction of SnO 2 /ZnO nanocomposite boosts the photocatalytic degradation efficiency of individual components under UV light irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…S. pyogene and S. aureus are more resistant to SnO2 NPs than K. pneumoniae and E. coli. Preethi et al [118] tested the antibacterial behaviour of Fe/SnO2 against E. coli using the colony count technique, and they found that the inhibition rates were 49, 65, 70, and 78% for pure, 0.01, 0.03, and 0.05 M, respectively. Anuja et al [121] studied the antibacterial activity of Al-Bi co-doped/SnO2 and found the zone of inhibition in the range of 20 to 36 mm against S. aureus, 25 to 34 against B. cereus and 30 to 41 against E. Coli.…”
Section: Some Important Current Studiesmentioning
confidence: 99%
“…The material's structure, surface morphology, composition, optical properties, photocatalytic dye degradation, and antibacterial properties are all thoroughly examined [ 26 ]. Previous studies reported that increasing the concentration of Fe-doped ions improved photocatalytic degradation efficiency and antibacterial activity [ 27 ]. Particularly, metal and metal oxide NPs are thought to have antibacterial activity due to the generation of reactive oxygen species such as H 2 O 2 , superoxide, and hydroxyl radicals.…”
Section: Introductionmentioning
confidence: 99%